Developing STEM students’ worksheet to improve students' creative thinking ability - Khairunnisa Pasaribu; K. Khairuna; Miza Nina Adlini; Fadhlan Muchlas Abrori (Universitas Muhammadiyah Malang, 2023)
Changes in the learning paradigm that prioritizes the optimization of creative thinking skills require a lot of consistent innovation and development. This study aims to develop students' worksheets based on STEM on viruses. This development research uses a 4D model by Thiagarajan. The instruments used in this study included interview sheets, validation sheets for content experts and media experts, questionnaires for biology teacher responses, and questionnaires for student responses, as well as tests. Product effectiveness on students' creative thinking skills was carried out using a pretest-posttest design and analyzed using the N-gain calculation. The results showed that the STEM-based students' worksheets on the Virus material that was developed received an assessment of 98% from content experts and 87% from media experts with very valid criteria. The responses of teachers and students were 93.3% and 90% respectively with very practical criteria. The developed STEM-based students' worksheets are also effective in increasing students' creative thinking skills by 0.75 with moderate criteria. These results indicate that STEM-based students' worksheets are appropriate for use in learning to improve students' creative thinking abilities.